Agriculture by Irrigation Modifies Microbial Communities and Soil Functions Associated With Enhancing C Uptake of a Steppe Semi-Arid Soil in Northern Patagonia - Frene, Juan P.; Faggioli, Valeria; Covelli, Julieta; Reyna, Dalila; Gabbarini, Luciano A.; Sobrero, Patricio; Ferrari, Alejandro; Gutierrez, Magalí; Wall, Luis G. (Frontiers in Soil Science, 2022)
The transformation of the semiarid steppe soil after five years of intensive irrigated agriculture in Northern Patagonia was analyzed in an on-farm study. The private grower venture used conservative practices, including no-till to maintain soil structure, high crop rotation and cover crops. To characterize steppe soil changes by irrigated agriculture, we analyzed the enzymatic activities involved in the biogeochemical cycles (carbon, nitrogen, phosphorus and sulfur), the whole soil fatty acids profile, the state of soil aggregation, and the bacterial and fungal microbiota through DNA sequencing methods. After five years of management, irrigated agriculture soil increased organic matter (25-33%), enzymatic activities -Cellobiose-hydrolase (60-250%), Phosphatase (35-60%), Xylanase (101-185%), Aryl-sulphatase (32-100%), Chitinase (85%), b-Glucosidase (61-128%), Leucine-aminopeptidase (138%) - depending on soil series, and macro-aggregate formation at the expense of the abundance of micro-aggregates in the first 0-5 cm of soil. Whole soil fatty acids profiles changed, enhancing mono-unsaturated, branched, cyclic and methylated fatty acids. Microbial communities showed significant differences between irrigated agriculture sites and pristine valleys. The richness-based alpha-diversity established increased bacterial communities but decreased fungal communities in cultivated soil. Indicators selected using the LEfSe method revealed the bacterial taxa Acidothermus, Conexibacter and Thermoleophilum, associated with semiarid steppe soil while Asticcacaulis, Aquicella and Acromobacter with irrigated agriculture. Ascomycota Phylum changed its community composition, being both taxa Aspergillus and Alternaria reduced while Stagonospora and Metarhizium were enhanced in irrigated agriculture. Taxa belonging to Acidobacteria, Chloroflexi, and Betaproteobacteria, that were enriched in irrigated agriculture soils, were associated with higher capture of C but smaller values of aggregation, while taxa abundant on steppe soils belonging to Actinobacteria, Alphaproteobacteria, and Firmicutes were positively associated with soil aggregation but negatively with C uptake.